2017
DOI: 10.29328/journal.jnpr.1001005
|View full text |Cite
|
Sign up to set email alerts
|

Foot Arch Differences in Elderly People at Standing: Considering Gender and Age

Abstract: Background:The foot is an important and complex structure that provides support, balance and propulsion to locomotion, thus, its proper care can help to have a better life quality avoiding pain. The medial longitudinal arch is an important structure that is related to injury risks when it shows some impairment. The purpose of this study was to characterize the foot arch index in people in relation to age and gender. Methods:The sample was composed of a total of 122 subjects, 79 healthy young subjects (40 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(21 reference statements)
1
1
1
Order By: Relevance
“…Other studies showed greater hallux pressure in individuals with hallux valgus than in controls [25,27]. A trend of higher forces under the medial forefoot could be due to the decreased height of the medial longitudinal arch owing to aging, as our participants were elderly women and it is known that the medial arch decreases in height with age [15,44]. This fact was previously reported by Hagedorn et al [15] who investigated elderly aged 66.2±10.5 years old.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Other studies showed greater hallux pressure in individuals with hallux valgus than in controls [25,27]. A trend of higher forces under the medial forefoot could be due to the decreased height of the medial longitudinal arch owing to aging, as our participants were elderly women and it is known that the medial arch decreases in height with age [15,44]. This fact was previously reported by Hagedorn et al [15] who investigated elderly aged 66.2±10.5 years old.…”
Section: Discussionsupporting
confidence: 71%
“…This fact was previously reported by Hagedorn et al [15] who investigated elderly aged 66.2±10.5 years old. A lower medial arch pronates the foot [44] and we think it is the cause of higher load on the medial forefoot. This could be the reason we found no changes between NORM and HVG groups in this study, as both groups' participants are relatively elderly women.…”
Section: Discussionmentioning
confidence: 79%
“…Although most studies [3], [10], [14] state that with age, the plantar arch sags, elderly people presenting with flat feet, in our research, after static analysis, the subjects presented pes cavus. In the elderly group, only 15% have a normal foot, while 85% have a pes cavus.…”
Section: Discussioncontrasting
confidence: 54%